Work-from-home and cities - Brueckner, Jan K. (CESifo, 2024)
This paper analyzes the urban impacts of hybrid WFH in the simplest possible model, relying on Leontief utility and production functions and other simplifying assumptions. The analysis shows that introduction of WFH raises both the wage and land consumption of households while shrinking the size of the business district and reducing business land rent. When WFH requires home work-space, the city’s overall spatial size increases, with residential rents rising in the suburbs while falling near the center. The decline in business rent and the rotation of the residential rent contour match empirical evidence showing that WFH reduces oﬃce-building values and ﬂattens the residential rent gradient.
10419/300049
Keywords: Graue Literatur; work from home; cities; commuting; land rents; productivity